Socio-economic impact of forage development on farm households livelihood in Mieso District, West Hararghe Zone, Oromia National Regional State - Ahmed, I. (Haramaya University, 2012)
Livestock and their products are becoming an important market-oriented commodity in Ethiopia. This study aims at shedding some lights on the ex-post potential socio-economic impact of improved forage development on farm households’ livelihood improvement. It does so through an empirical investigation of the impact of forage technology adoption on income, health, education, reduced job burden of women, saving of school time of children and nutritional status of 120 sampled farm households in Mieso district. As technology adoption is randomly assigned, the study used non-parametric ‘p-score matching analysis’ in assessing the ‘causal’ effect of the improved forage technology on farm-households’ livelihood. This method was checked for covariate balancing test with standard bias, t-ratio and joint-significance level test. Descriptive and econometric methods are used to analyze the data. Of the 120 sampled households, improved forage technology users were 60 and the rest were non-users. Descriptive analyses of t-test and test results shows the existence of significant mean and proportion difference between users and non-users in terms of education, active labor force, land size, fattening experience, livestock ownership, information accesses, participation in demonstration days and accesses to credit which shows the descriptive results improved forage have positive impacts on outcome of the studies income, women work time, children study time, health and education expense at 1% significant level, while nutrition status at 5% significant level. Also market-oriented livestock product sold Milk, Butter, Cattle, and Shoat affects at 1% level, while Honey and Camel at 5% and 10% percent level. Propensity score matching analysis also show that adoption of improved forage technology have significantly and positively affected by active labor force, information accesses, fattening experience, demonstration day, and livestock holding while age, family size and market distances have a significant negative effect. The sensitivity analysis also shows that the impact result estimates are insensitive to unobserved selection bias. Overall, the adoption of improved forage on socio-economic livelihood have significant positive impact on the households’ total income, income from livestock sale, reducing women job burden, saving school time of children and expenditures on health status. The thesis finally discusses these results in detail and draws some recommendations. So it is recommended to scale up and out the adoption of the improved forage technology to other farmers in the district as well to other regions with similar socioeconomic characteristics.